TINJAUAN YURIDIS TANGGUNG JAWAB NOTARIS DALAM PEMBUATAN SURAT WASIAT BERDASARKAN UNDANG-UNDANG NOMOR 2 TAHUN 2014 TENTANG JABATAN NOTARIS - Muh Syarifuddin; Nasti Aisyah Bani Naswan (Jurnal Ilmu Hukum Kanturuna Wolio, 2026)
This research is motivated by the conflict of norms between the applicable regulations  and  the  reality  that  occurs  in  the  field.  Law  Number  2  of  2014. Concerning the Position of Notary does not clearly explain what are the responsibilities of a Notary in making authentic deeds, especially wills. The purpose of this study is to determine the responsibilities of a Notary in making a will and how to implement a will if the Notary who is given the mandate has retired. The results of the study indicate that the responsibility of a Notary in making a will is only to store the letter. A will is not a Notary product. This means that a Notary is not responsible for the contents of the will. The contents of the will are a unilateral will made by someone and stated in the form of a will. The implementation of a will even though the Notary who is entrusted has retired is still carried out as it should be. A Notary who has retired before entering his retirement period is required to submit a protocol during his term of office to the replacement Notary he has appointed and the replacement Notary is willing. This aims to ensure that all duties and responsibilities of a Notary can still be carried out in accordance with applicable procedures